Punctuated growth of InAs quantum dashes-in-a-well for enhanced 2-μm emission - Chu, Rafael Jumar Abella; Kim, Yeonhwa; Woo, Seungwan; 최원준; 정대환 (SPRINGER, 2023)
InAs quantum dashes (Qdash) engineered to emit near 2 mu m are envisioned to be promising quantum emitters for next-generation technologies in sensing and communications. In this study, we explore the effect of punctuated growth (PG) on the structure and optical properties of InP-based InAs Qdashes emitting near the 2-mu m wavelength. Morphological analysis revealed that PG led to an improvement in in-plane size uniformity and increases in average height and height distribution. A 2 x boost in photoluminescence intensity was observed, which we attribute to improved lateral dimensions and structural stabilization. PG encouraged formation of taller Qdashes while photoluminescence measurements revealed a blue-shift in the peak wavelength. We proposed that the blue-shift originates from the thinner quantum well cap and decreased distance between the Qdash and InAlGaAs barrier. This study on the punctuated growth of large InAs Qdashes is a step toward realizing bright, tunable, and broadband sources for 2-mu m communications, spectroscopy, and sensing.